SISTEM INFORMASI PENJUALAN ACCESSORIES BERBASIS WEB PADA TOKO FAHMI JAKARTA - Henny Destiana; Annisa Hadidah (Paradigma, 2016)
Store Fahmi Accessories Jakarta is a shop that serves the sale of various kinds of accessores. Adaptable web information systems can be the most efficient means of promotion and information resources that can be beneficial to users. And of course in a web-based information systems can be provided for the sale of online-based (e-commerce). The purpose of this system design is to develop information systems, web-based online sales and provide a variety of information about the Shope Fahmi Accessories Jakarta and simplify the admin to manage the order data and make periodic reports according to the existing transaction data. The program is also designed to facilitate customers in the buying process online that can be done within 24 hours and as a promotional strategy to increase sales volume at the Shop Fahmi Accessories Jakarta. The research method used is the analysis of research and data collection . The results of this study resulted in the system design online Accessories Sales. The system is designed using PHP as a programming language and MySQL as the processing of existing data on this system. And a virtual server using the APPServ web browser to display the system information of this sale.